Interleukin (IL)-4 Induces Leukocyte Infiltration In Vivo by an Indirect Mechanism. (4th August 2009) - Ratthé, Claude; Ennaciri, Jamila; Garcês Gonçalves, David M.; Chiasson, Sonia; Girard, Denis
Abstract : Interleukin (IL)-4 is a cytokine known mainly for its anti-inflammatory activity. Using the in vivo murine air pouch model, we found that IL-4 significantly increased the number of leukocytes after 9 hours of treatment, consisting mainly of neutrophil (60%) and monocytic (40%) cell populations. Using an antibody array, we found that the expression of several analytes (predominantly CCL2) was increased by IL-4 before the arrival of leukocytes. The IL-4-induced expression of CCL-2 was confirmed by ELISA. Air pouch resident lining cells were harvested and were found to express IL-4Rα . CCL2 mRNA expression was monitored in lining cells, cells isolated from the air pouch skin, in RAW264.7 macrophage and in epithelial Mode-K cells and its expression was increased in response to IL-4 in all conditions. We conclude that IL-4 can attract leukocytes in vivo by an indirect mechanism involving the production of several analytes by, at least, resident cells.